2021
DOI: 10.3390/life11080863
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Thaumatin-like Protein Gene (LeTLP1) Endows Resistance to Trichoderma atroviride in Lentinula edodes

Abstract: Lentinula edodes (shiitake mushrooms) is heavily affected by the infection of Trichoderma atroviride, causing yield loss and decreases quality in shiitake mushrooms. The selection and breeding of fungal-resistant L. edodes species are an important approach to protecting L. edodes from T. atroviride infection. Herein, a highly resistant L. edodes strain (Y3334) and a susceptible strain (Y55) were obtained by using a resistance evaluation test. Transcriptome analyses and qRT-PCR detection showed that the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Structure prediction for an A. ostoyae developmentally expressed protein indicated an acidic cleft in the 3D structure, characteristic of antimicrobial members of the family (Krizsán et al 2019). A new report of antifungal activity of the thaumatin-like protein Le.TLP1 in L. edodes further supports putative defense roles for the GH152 family (Ma et al 2021).…”
Section: Gh5 -mentioning
confidence: 64%
“…Structure prediction for an A. ostoyae developmentally expressed protein indicated an acidic cleft in the 3D structure, characteristic of antimicrobial members of the family (Krizsán et al 2019). A new report of antifungal activity of the thaumatin-like protein Le.TLP1 in L. edodes further supports putative defense roles for the GH152 family (Ma et al 2021).…”
Section: Gh5 -mentioning
confidence: 64%
“…To date, more than forty Trichoderma species have been reported to be associated with mushroom green mold disease. Trichoderma atroviride , T. harzianum , T. koningii , T. longibrachiatum , T. pseudokoningii , and T. viride are the six most commonly cited species causing disease on edible mushrooms ( Table 2 ), all of which could infect six to eleven species of cultivated mushrooms [ 61 , 64 , 68 , 73 , 83 , 91 , 119 , 122 , 123 ]. Before this study, there were seven known species that could cause G. sichuanense diseases, namely, T. koningii, T. longibrachiatum , T. pseudokoningii , T. viride , T. atrobrunneum , T. ganodermatis [ 47 ], and T. hengshanicum [ 87 ], while T. orientale can cause disease on G. applanatum [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arl2 is involved in regulating mitochondrial transport and apoptosis [41], and these signaling pathway regulated by genes are responsible for the color change of L. edodes. Heat stress and trichoderma stress can pose fatal damage to L. edodes [16,42] . Our data showed that each of 5 Le-small GTPase subfamilies such as Rho and Ran made the response to heat stress and trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress and the infection of Trichoderma spp. could cause huge losses for L. edodes cultivation in China and other Asian cultivation area [1,16,17]. The small GTPases play important roles in physiological processes such as environmental stress response and changing intracellular metabolic flow in fungi [3].…”
Section: Researchmentioning
confidence: 99%